Effects of Visible and Invisible Hyperlinks on Vocabulary Acquisition and Reading Comprehension for High- and Average-Foreign Language Achievers - Ofelia R. Nikolova (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This study investigated the effects of visible and invisible links for annotated words in a computer module for learning French on the vocabulary acquisition and reading comprehension of two types of students – high- and average- achievers. Two hundred and sixty-four second-semester students of French were identified as high- or average-achievers. Each type of students was then randomly assigned to two groups – with visible or invisible hyperlinks. All students were instructed to read a short passage in French (181 words) for general comprehension and allowed to consult the annotated words (made visible by bold face for the visible links group) as much as they needed. The students took a vocabulary pretest and an immediate and delayed (two weeks) vocabulary and reading comprehension posttest. The results of the study showed that average- achievers benefited more from the visible links for vocabulary acquisition and reading comprehension than high- achievers. The results are discussed in light of second language acquisition and gifted-student theories and suggestions for future research are made.